2010
DOI: 10.1681/asn.2009111153
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the EGFR Inhibitor Erlotinib on Magnesium Handling

Abstract: A mutation in pro-EGF causes isolated hypomagnesemia, and monoclonal antibodies targeting the extracellular domain of the EGF receptor (EGFR) affect epithelial Mg 2ϩ transport. The effect of the EGFR tyrosine kinase inhibitor erlotinib on Mg 2ϩ homeostasis, however, remains unknown. Here, we injected C57BL/6 mice with erlotinib for 23 days and observed a small but significant decrease in serum Mg handling but its effect on the systemic Mg 2ϩ concentration seems less potent than that observed with antibody-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 21 publications
1
41
0
Order By: Relevance
“…Although proton pump inhibitors most likely cause impaired intestinal magnesium absorption, most of the other drugs associated with hypomagnesemia impair renal tubular magnesium reabsorption by direct or indirect inhibition of magnesium reabsorption in the thick ascending limb or the distal convoluted tubule (102,110,111).…”
Section: Clinical Consequences Of Alterations In Magnesium Balancementioning
confidence: 99%
“…Although proton pump inhibitors most likely cause impaired intestinal magnesium absorption, most of the other drugs associated with hypomagnesemia impair renal tubular magnesium reabsorption by direct or indirect inhibition of magnesium reabsorption in the thick ascending limb or the distal convoluted tubule (102,110,111).…”
Section: Clinical Consequences Of Alterations In Magnesium Balancementioning
confidence: 99%
“…Although these drugs may induce hypomagnesaemia, the lack of severity effect on serum Mg 2+ concentration seems to be related to the typical human doses of these small molecules, as it was shown by Dinke et al in an experimental data [28]. Using a C57BL/6 mice and HEK293 cells expressing TRPM6 treated with different concentrations of erlotinib, they established that erlotinib is able to influence Mg 2+ handling but its effect on the serum Mg 2+ concentration seems less potent than that observed with anti-EGFR antibodies [28]. Although EGFR tyrosine kinase inhibitors have also the potential to induce hypomagnesaemia, the usual human doses seem to be insufficient to induce this side effect.…”
Section: Hypomagnesaemia Induced By Targeted Anti-egfr Agentsmentioning
confidence: 85%
“…4,6,16,17,19,24 TRPM6 undergoes autophosphorylation, 24,25 which leads to a shift in the inhibition by intracellular Mg 2+ /Mg 2+ nucleotides to higher concentrations. 17 In the kidneys, TRPM6 is regulated by the EGF, [26][27][28] insulin, 29 estrogens, 30,31 purinergic signaling, 32 dietary Mg 2+ intake, 30 and acid-base status. 33 Previous studies have suggested increased DCT Mg 2+ reabsorption in response to hormones such as parathyroid hormone (PTH), glucagon, calcitonin, and arginine vasopressin.…”
Section: +mentioning
confidence: 99%